Stanisław Grochowski’s “Pamiątka nagrobna Samuela Głowy” – cycle of poems and its author - Pilarz, Norbert (Melusine. Old Literature and Culture, 2024)
The main focus of the article is the critical edition of Stanisław Grochowski’s hitherto unpublished work, “Pamiątka nagrobna Samuela Głowy”. This includes a critical apparatus in which changes in the three available copies, each representing a diﬀerent variant, are noted. For instance, I have listed the added fragments present in the copies and lexical changes, which assisted in determining the possible order in which variants were printed. In the introduction, I brieﬂy introduced the motifs employed by the poet, such as the deviation from traditional genre conventions (for example, by modifying panegyric principles of funeral poetry) and connections with Jan Kochanowski’s poems. I compared how the jester was portrayed in Grochowski’s cycle with Kochanowski’s “Fraszki”.